The Impacts of Performance Appraisal on Employee’s Job Satisfaction and Organizational Behavior - Abdul Basir Hamidi (Ilomata International Journal of Social Science, 2023)
The implementation of performance appraisal is widespread, and it is a significant tool by which organizations can maximize the potential of human resources. The purpose of this study is to investigate how performance appraisal affect employee’s job satisfaction and organizational behavior. The methodology used for this research is a qualitative-library research, entailing the data collections and analyses from published resources such as books, journals, and internet databases. Based on the results, it was found that the experience of a positive performance appraisal raises not only workers’ sense of accomplishment but also self-worth and fosters the trust in the legitimacy process. Furthermore, appraisal assists employee retention by highlighting the company's dedication to address their requirements and support the development. In order to increase job satisfaction and organizational behavior, the study emphasizes the values of giving feedback to employees, defining goals, encouraging employee involvement, and carrying out efficient performance appraisal.